Farnesol, the farnesol pathway, and the immune-gut-brain axis - Gates, Megan; Schumacher, Sean M.; Doyle, William J.; Sofaly, Natalie; Roullet, Jean-Baptiste; Ochoa-Repáraz, Javier (Frontiers in Pharmacology, 2026)
Experimental models and clinical evidence suggest that the gut and the central nervous system (CNS) interact in a multifactorial, bidirectional manner. A third player, the immune system, has recently been identified in these interactions, with research linking the gut microbiome to inflammatory conditions, including those affecting the CNS. The molecular signals involved in communication between the gut, brain, and immune system have been extensively studied. However, no unique signaling pathway has been identified for each component of the immune-gut-brain (IGB) axis to date. In this review, we argue that isoprenoids, and specifically farnesol, are key signaling molecules that link the gut and its microbiota, the immune system, and the CNS. The pharmacological properties of farnesol, an intermediate in the broadly conserved mevalonate pathway, are diverse and encompass quorum sensing and microbial biofilm inhibition, neuroinflammatory protection, and modulation of intracellular calcium (Ca2+) signaling pathways. Many of these signaling pathways are implicated in neuron-to-neuron communication and in the responses of immunocompetent cells to immunogenic stimuli. We will first address the biological relevance of the immune-gut-brain axis and the gut microbiome in regulating health and disease. Next, we will review the molecular and cellular mechanisms by which farnesol regulates both the gut microbiota and the host’s innate and adaptive immune systems. Finally, we will provide a perspective on the immunoregulatory mechanisms underlying farnesol’s protective properties in models of neuroinflammatory diseases. In summary, we propose a review of the most salient studies that establish farnesol as a significant modulator of the immune-gut-brain axis.